α decay energies and half-lives from a macroscopic-microscopic model - 彭金松 李璐璐 周善贵 赵恩广 (Chinese physics C, 2008)
α decay energies of 323 heavy nuclei with Z ≥82 are evaluated with a macroscopic-microscopic model. In this model, the macroscopic part is treated by the continuous medium model and the microscopic part consists of shell and pairing corrections based on the Nilsson potential. α decay half-lives are calculated bY Viola-Seaborg formula. The results of α decay energies and half-lives are compared with experimental values and satisfactory agreement is found. The recoiling effect of the daughter nucleus on α decay half-life is also discussed.